Self-resolving focal non-ossifying myositis: a poorly known clinical and imaging entity diagnosed with MRI. (27th November 2015) - Perlepe, Vasiliki; Dallaudière, Benjamin; Omoumi, Patrick; Hristova, Lora; Rezzazadeh, Afshin; Vande Berg, Bruno; Malghem, Jacques; Lecouvet, Frederic
Background: Focal myositis is a rare benign inflammatory pseudotumor, presenting as a painful nodular mass within a muscle, and characterized by spontaneous resolution within weeks. Purpose: To assess the clinical and imaging findings of focal nodular myositis simulating a neoplasm at clinical examination, with no history of trauma. Material and Methods: This study describes the locations and appearance at ultrasonography (US), computed tomography (CT), and magnetic resonance imaging (MRI) of this condition in a series of five patients. Results: MRI and US displayed a solid intramuscular "tumor" and suggested a continuum between the proximal and distal muscle fibers that appeared thickened within the nodular lesion, a sign that has been reported in myositis ossificans. MRI showed edema in adjacent muscles and soft tissues, as well as intense enhancement of the mass. Intense vascular flows were seen at Doppler analysis. CT did not reveal the appearance of peripheral ossifications, ruling out the diagnosis of myositis ossificans. In some patients, the diagnosis of sarcoma had been suggested as possible by the radiologist. Imaging follow-up with MRI showed complete resolution of the masses over several weeks, thus avoiding a biopsy; no recurrence was observed at long-term follow-up (more than 24 months). Conclusion: This paper highlights MRI and US findings in focal non-ossifying myositis, and emphasizes the role of MRI in suggesting this diagnosis, leading to the careful follow-up of the lesion until its resolution, and ruling out more aggressive lesions.